Involução uterina no pós-parto em vacas leiteiras - Mello, Silvio Valladão Ferreira (2016)
Reproductive failure is a major cause of culling cows and economic loss. The reproductive efficiency is one of the critical points for system profitability. Thus, a better reproductive performance is associated with a shorter and more physiological puerperium. In the present experiment a total of 52 dairy cows on a free-stall system were evaluated. The cows were allocated into two experimental groups, primiparous (n = 24) and multiparous (n = 28). At the parturition, body condition scores were accessed. At the third, fourth and fifth weeks postpartum the uterus was examined by rectal palpation and ultrasonography, assessing consistency, position and size of the uterine horns. Also, it was collected age, date of birth, milk production in the third, fourth and fifth weeks, days in milk, postpartum pathologies, and the dates of artificial insemination. There was no statistical difference in uterine involution between primiparous and multiparous. Regarding to presence of pathologies, 33.33% of primiparous and 64.71% of multiparous showed no uterine involution. The interval from calving to first insemination was shorter in cows presenting no pathologies when compared to those whose presented any pathology at postpartum. Also, the interval from calving to first insemination was shorter in primiparous when compared to multiparous. However, the uterine involution does not interfere with interval from calving to first insemination. It is suggested that it might exist a subclinical condition influencing uterine involution in dairy cows.